An optical-fiber sensor based on time-gated fluorescence for detecting water content in organic solvents. Issue 11 (7th June 2015) - Huang, Dawei; Bing, Yongxin; Yi, Hao; Hong, Wei; Lai, Cui; Guo, Qingwei; Niu, Chenggang
<x xml:space="preserve">Abstract</x> A stable and highly sensitive optical-fiber sensor based on time-gated fluorescence for water content determination in organic solvents was proposed in this paper.